Factors associated with hypotension during the first hour of continuous renal replacement therapy in critically Ill patients: A prospective observational study - Mengdie Xue; Suying Lu; Chenglin Zhao; Zheyao Zhang; Jing Yang; Zhiyu Mao; Jingjuan Xu (PLoS ONE, 2025)
Purpose To investigate the factors of hemodynamic instability within the first hour of continuous renal replacement therapy (CRRT) in critically ill patients. Materials and methods A prospective observational cohort study of patients admitted to the intensive care unit (ICU) and underwent CRRT between January 17, 2024, and December 25, 2024, was conducted. The least absolute shrinkage and selection operator (LASSO) regression was used to screen potential factors and a multivariate logistic regression model was performed to determine the independent factors of hypotension within the first hour of CRRT. Results Hypotension occurred in 166 out of 435 patients (38.2%). Female (OR=0.53, 95%CI:0.3–0.89), the use of colloidal solutions (OR=0.23, 95%CI:0.12–0.46), platelet count (PLT) (OR=0.99, 95%CI:0.99–0.99), and baseline mean arterial pressure (MAP) (OR=0.95, 95%CI:0.93–0.96) were recognized as protective factors against hypotension within the first hour of CRRT in critically ill patients. Older age (OR=1.02, 95%CI:1.01–1.04), mechanical ventilation (OR=2.59, 95%CI:1.28–5.23), ultrafiltration rates of 101-200 mL/h (OR=2.04, 95%CI:1.11–3.75), international normalized ratio (INR) (OR=1.78, 95%CI:1.02–3.09), and high myoglobin level (OR=1.01, 95%CI:1.01–1.01) were identified as significant risk factors. Baseline MAP and mechanical ventilation are the most important predictors of hypotension within the first hour of CRRT in critically ill patients. Conclusions The incidence of hypotension within the first hour of CRRT in critically ill patients was 38.2%. Female, PLT, baseline MAP are protective factors, and age, mechanical ventilation, ultrafiltration rate of 101-200ml/h, INR, myoglobin are risk factors for hypotension within the first hour of CRRT in critically ill patients.